Two new species of Coenagrion Kirby, 1890, from China (Odonata: Zygoptera: Coenagrionidae) - Yu, Xin; Bu, Wenjun (Zootaxa, 2007)
Two new species of Coenagrion Kirby (Coenagrion aculeatum, sp. nov., holotype male, China, Chongqing, Jiangjin, 23V-2001, deposited in Life Sciences College of Hebei University, Baoding, China; and C. tengchongensis, sp. nov., holotype male, China, Yunnan, Tengchong, Zhengding, 1800m, 15-VIII-2006, deposited in Institute of Entomology, Nankai University, Tianjin, China) are described, and diagnostic figures of caudal appendages and genital ligulae are provided.